Investigação da atividade antifúngica, mecanismo de ação e análise do perfil proteico de Trichophyton rubrum E Microsporum canis frente a derivados de Piper umbellatum - Freitas, Jolindo Alencar [UNESP] (2015)
Piper umbellatum L. Miq. is a plant belonging to the Piperaceae family found in all regions of Brazil and traditionally used for various diseases and disorders. This work evaluates the antifungal activity of P. umbellatum against clinical isolates of Microsporum canis and Trichophyton rubrum by the determination of minimal inhibitory concentration (MIC).The phytochemical study of hexane and ethanol extracts of the aerial parts of Piper umbellatum led to the isolation of two substances, sesamin and 4-nerolidylcatechol (4NC). When tested against M. canis, the ethanol extracts showed MIC value of 39.06 μg/mL meanwhile the chloroform and ethyl acetate extracts showed MICs value of 78.13 μg/mL and the hexane extract showed MIC of 1250 μg/mL, the MIC value of fluconazole used as control was 16 μg/mL. The fractionation of the ethanol extract led to obtain of fraction 11 that presented the best MIC between the fractions, of 9.77 μg/mL to M. canis. 4NC was obtained from fraction 11 and presented the best MIC in this study, 2.44 μg/mL for M. canis and 4.88 μg/mL, for T. rubrum. M. canis showed a change in the protein profile in SDS-PAGE after treatment with 4NC, with the appearance of bands of approximately 139 and 30 kD intracellular protein and 35 and 15 kDa in extracellular protein, each of those bands was analyzed through LC-MS/MS (MALDI-TOF/TOF). The ethanolic extract wasn‟t citotoxic until 500 μg/mL, while 4NC presented IC50 values of 18.3 and 31.5 μg/ml to Hep G2 and MRC-5 cell lines.